Less paper, more efficiency - Baker, Glenn (NZ Business, 2011)
Reports on the possibilities of modern multifunctional devices (MFDs, printer/copiers/scanners/faxes) twinned with document management systems (DMS). Talks to Greg Twiname of Konica Minolta and Richard Penny of Fuji Xerox New Zealand about whether a 'paperless office' is realistic, and scanning, digitising and tracking documents. looks at the features in the latest generation of MFDs and how these might be used to gather information and automate workflows. Notes the environmental benefits through reducing printing and energy usage. Notes the cost savings, and the possible future developments in using DMS. Lists related websites. Gives a case study of a law firm in Christchurch using digital archiving. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.